2017
DOI: 10.1016/j.jallcom.2016.09.322
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing single red band upconversion luminescence of KMnF3:Yb3+/Er3+ nanocrystals by Mg2+ doping

Abstract: In this work, monodisperse Mg 2+ doped KMnF3:Yb 3+ /Er 3+ nanoparticles (NPs) are prepared via a fast solvothermal method. With the excitation of 980 nm laser diode, a brightly single red upconversion (UC) luminescence can be observed from KMnF3:Yb 3+ /Er 3+ NPs, which is further improved by introducing Mg 2+ ions. Moreover, the single red UC fluorescence intensity of the KMnF3:Yb 3+ /Er 3+ NPs co-doped with 30 mol% Mg 2+ ions is enhanced by 20.8 times compared to that of Mg 2+ ions-absent sample. Besides, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…( + 1, 2+, ) = (6,3+, ) + ∆ ( , 6, 3 +) The alteration of the host matrix would result in the variation in phonon energy that leads to different upconversion energy transfer pathways. There are numerous observations of structure-dependence of upconverting nanocrystals, especially those with alteration of lattice symmetry [39,43,45,[66][67][68]. A higher enhancement of luminescence emission has been reported for ZrO2:Er 3+ in the monoclinic phase than in the tetragonal phase [69].…”
Section: Host Matrix Screeningmentioning
confidence: 99%
“…( + 1, 2+, ) = (6,3+, ) + ∆ ( , 6, 3 +) The alteration of the host matrix would result in the variation in phonon energy that leads to different upconversion energy transfer pathways. There are numerous observations of structure-dependence of upconverting nanocrystals, especially those with alteration of lattice symmetry [39,43,45,[66][67][68]. A higher enhancement of luminescence emission has been reported for ZrO2:Er 3+ in the monoclinic phase than in the tetragonal phase [69].…”
Section: Host Matrix Screeningmentioning
confidence: 99%
“…For example, different impurity ions/elements such as, Ca 2+ , Mg 2+ , Zn 2+ , and Li + ions improves the emission of Yb 3+ /Er 3+ codoped phosphors. [10][11][12][13] Bismuth ion is non-toxic, cheap, has wide excitation and emission band, and is good non-rare earth doping sensitized ion. Bismuth ion radius is 1.03 Å, slightly greater than the radius of Y 3+ as 0.89 Å. Mingzhu Yang et al reported the significantly enhanced emission intensity of bismuth ions doped Y 2 O 3 :Yb,Er.…”
Section: Introductionmentioning
confidence: 99%
“…Fluorides such as NaMF 4 (M ¼ Y and Gd), KMnF 3 and CaF 2 have been extensively studied as host of UC phosphors because they have low photon energies and good emission properties. [20][21][22] Also, thanks to the development of various nanoparticle synthesis technologies, uoride nanoparticles have been applied as an optical probe in biomedical applications. [23][24][25][26] However, in order to obtain controlled highquality particles having good UC characteristics, the uoride requires an expensive organometallic precursor and a toxic organic solvent.…”
Section: Introductionmentioning
confidence: 99%